1989
DOI: 10.1136/jnnp.52.12.1351
|View full text |Cite
|
Sign up to set email alerts
|

Source of pain and primitive dysfunction in migraine: an identical site?

Abstract: SUMMARY Twenty common migraine patients received a one sided frontotemporal application of nitroglycerin (10 patients) or placebo ointment (10 patients) in a double blind study. Early onset migraine attacks were induced by nitroglycerin in seven out of 10 patients versus no patient in the placebo group. Subsequently 20 migraine patients, who developed an early onset attack with frontotemporal nitroglycerin, received the drug in a second induction test at other body areas. No early onset migraine was observed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…Since there is a substantial pulmonary clearance of ET‐1, with a mean first‐pass clearance of approximately 50%, an explanation for this could be that a higher concentration of intravascular ET‐1 would reach the cerebral circulation in patients with a PFO. Another, more likely, explanation is based on the observation that microemboli, for example, in the form of air bubbles, entering the cerebral circulation can induce CSD in animals and that intravenous administration of agitated saline in migraine patients with PFO may occasionally induce migraine aura . Further, rare occurrences of suspected transient ischemic attacks and neuroimaging‐verified ischemic stroke following sclerotherapy have been reported almost exclusively in patients with right‐to‐left cardiac shunts, mostly PFOs .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since there is a substantial pulmonary clearance of ET‐1, with a mean first‐pass clearance of approximately 50%, an explanation for this could be that a higher concentration of intravascular ET‐1 would reach the cerebral circulation in patients with a PFO. Another, more likely, explanation is based on the observation that microemboli, for example, in the form of air bubbles, entering the cerebral circulation can induce CSD in animals and that intravenous administration of agitated saline in migraine patients with PFO may occasionally induce migraine aura . Further, rare occurrences of suspected transient ischemic attacks and neuroimaging‐verified ischemic stroke following sclerotherapy have been reported almost exclusively in patients with right‐to‐left cardiac shunts, mostly PFOs .…”
Section: Discussionmentioning
confidence: 99%
“…A robust method for experimental provocation of migraine aura, however, has not yet been established . Migraine provocation using vasodilating drugs (glyceryl trinitrate, calcitonin‐gene related peptide, and cilostazol) has been attempted in patients suffering from migraine with aura specifically . Interestingly, in these studies, the drugs generally induced migraine attacks without aura, even in patients who previously experienced attacks with aura exclusively, while migraine attacks with aura were only rarely triggered.…”
Section: Discussionmentioning
confidence: 99%
“…3 In the same patients, early onset migraine did not occur with nitroglycerin applied to the wrist, or to the asymptomatic temple in cases of unilateral migraine. In particular, studies by Wolff 1 led to the concept, which is still debated, that vasodilatation of the branches of the external carotid artery (middle meningeal artery and arteries of the scalp) is correlated with migraine pain.…”
mentioning
confidence: 83%
“…In patients suffering from migraine with aura (MWA) or migraine without aura (MWOA), a migraine attack can be triggered by nitroglycerin (NTG) 1‐3 . The number and the latency of successful inductions by NTG vary according to its route of administration: sublingual, 4 intravenous, 2 and transdermal 5 . Our study group demonstrated that topical NTG administration at the typical site of pain is a highly successful, rapid, and tolerated method of migraine induction 5,6 .…”
mentioning
confidence: 88%